Strategic Self-Praise in Anonymous Language Service Platforms: A Pragmatic Study of Dating Advertisements on QQ Zone Confession Wall in China - Yang, Jinlong; Chen, Qianyu; Yang, Muwen (Journal of Language Service Studies, 2026)
The development of the internet has made online socializing and partner seeking possible, thereby enabling single individuals to communicate and match with one another across temporal and geographical boundaries within virtual spaces. The rise of online dating has drawn scholarly attention from fields such as sociology, psychology, and linguistics, giving rise to a growing body of research on the topic. Digitally mediated communication, marked by reduced contextual cues, requires users to invest greater interpretive effort to reach mutual understanding. This study employs a combined pragmatic and language-service perspective to analyze self-praise strategies in dating advertisements on China’s QQ Zone Confession Wall. It explores how these strategies are utilized within the platform’s anonymous and community-mediated setting to build favorable identities and attain relational objectives. Results show that the distribution of unadorned explicit self-praise (47.22%) and modified explicit self-praise (47.22%) is the same, while the frequency of the implicit strategy is the lowest (5.56%). The study illustrates how users tactically make use of the platform’s language service features, which include anonymity, public communality, and multimodal affordances, to initiate relationships. This highlights the role of digital platforms not only as communication channels but as active mediators that influence pragmatic behavior in online courtship.